Regeneration of the British industrial towns: case of the town Barnsley - Kopeć, Marcin (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2009)
Polish cities need to redevelop post-industrial areas located within their boundaries. Cities’ authorities, while preparing regeneration programs, can use best practices of Western European cities. One very good example is the case of the English town Barnsley. Barnsley in earlier days was famous for coal mining, but the last pit was closed in 1994. With the demise of the coal industry, people suffered from unemployment and the town from losing its main revenue sources (in 2000, the town was ranked 16th out of 354 most deprived district of England). Town was blighted by a very high incidence of post-industrial areas: disused colliery spoil tips, pit yards and the railway infrastructure which served the collieries. For many years Barnsley has carried out an extensive land reclamation program, together with investments put into new road links and job creation schemes for the former colliery workers. Between 1982 and 2003, over 23 million GBP was spent on the restoration of over 600 hectares of derelict land. Barnsley’s vision is to be a 21st Century Market Town. Those plans are prepared for the next 30 years, and the budget of 380 million GBP (including EU co-financing) constitutes the basis for the town transformation. In 2002, the Barnsley Metropolitan Borough Council, together with local partners, started the Rethinking Barnsley weekend, a consultation project, which was the entry for preparing the urban centre regeneration program, called Remaking Barnsley. Planned and partly realised projects include construction of the new Barnsley Interchange - bus and coach station opened in May 2007, new cultural centre in the old Civic Hall, new commercial centre in Barnsley Markets, Digital Media Centre - opened in August 2007 - an incubator of new technologies, as well as new office and residential areas in the town centre. New business parks opened the new possibilities on the labour market. A well planned and perfectly realised process of the town development, started by wide citizens’ consultancy program, treated as a basis for establishing the town development vision, transformed then into an action plan and verified by already completed projects, is a good example to be copied by Polish towns.